Meta-Analysis: Effectiveness of Dental and Oral Health Education using Combination Method on Knowledge and Plaque Scores in Visually Impaired Childrenveness of Dental and Oral Health Education using Combination Method on Knowledge and Plaque Scores in Visually Impaired Children - Anis Nur Widayati; Didik Gunawan Tamtomo; Burhannudin Ichsan (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Dental health education is important to improve people's dental and oral health. Visually impaired children have limited vision, so they need appropriate and appropriate methods for accepting visually impaired children by maximizing the provision of education through senses other than sight in carrying out treatment and prevention efforts. This study aimed to analyze the effectiveness of combination oral health education on the oral health knowledge and plaque scores in visually impaired children. Subjects and Method: This was a meta-analysis with PICO model. Population: Visually impaired children. Intervention: dental health education ≥3 methods. Comparison: without education or <3 education methods. Outcome: oral hygiene knowledge and plaque scores. Article search was carried out using the keywords: (